2016
DOI: 10.1515/aoas-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Vitelline Membrane Strength and Selected Physical Parameters of Poultry Eggs

Abstract: the aim of this study was to evaluate the strength of vitelline membrane and its correlation with other morphological traits and the viscosity of egg yolk of different poultry species: goose, turkey, muscovy duck, chicken, guinea fowl and Japanese quail. vitelline membrane strength (vms) was defined as work and force after the deformation of yolk at 6 mm. Bird species affected the VMS of egg yolk. the lowest strength was measured for the vitelline membrane of goose egg yolk. there were no apparent differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…The effect of the laying period on weight, ratio, and color of the yolk was nonsignificant. Yolk weight found in the present study was lower than the value (75.4 g) reported by Adamski et al [27] for Biala Koludzka geese in the 3rd laying season and higher than the value (42.58 g) reported by Marzec et al [28] for 61-week-old White Koluda W11 geese. Biesiada-Drzazga et al [17] also reported that the effect of the laying period on yolk index was statistically nonsignificant.…”
Section: Internal Quality Traitscontrasting
confidence: 80%
“…The effect of the laying period on weight, ratio, and color of the yolk was nonsignificant. Yolk weight found in the present study was lower than the value (75.4 g) reported by Adamski et al [27] for Biala Koludzka geese in the 3rd laying season and higher than the value (42.58 g) reported by Marzec et al [28] for 61-week-old White Koluda W11 geese. Biesiada-Drzazga et al [17] also reported that the effect of the laying period on yolk index was statistically nonsignificant.…”
Section: Internal Quality Traitscontrasting
confidence: 80%
“…Dudusola (2009) investigated that YI of freshly laid quail egg was 0.40 as similar as to the present study. It has been reported that the yolk index of quail eggs has been ranged between 0.46 to 0.6 (Marzec, Michalczuk, Damaziak, Mieszkowska, Lenart, & Niemiec, 2016). Kokoszynski, Bernacki, and Korytkowska (2007) reported that yolk index of Peking duck at the beginning of laying period was 0.41.…”
Section: Comparison Of Village Chicken Shaver Brown Duck Turkey Anmentioning
confidence: 99%
“…These authors [7][8] have demonstrated that pattern and thickness of the fibers, as well as the presence of additional structures serving, inter alia, toward the consistency of IL and OL, differ among different species. The differences observed in the strength of VM in different poultry species also suggest different structures that form the membrane [14]. All the previously studied species belong to the precocial group, in which the offsprings are partially independent at clutching, that is, they are covered with down and move and feed themselves but are dependent on parental care.…”
Section: Introductionmentioning
confidence: 96%